Large-scale meta-analysis of interleukin-1 beta and interleukin-1 receptor antagonist polymorphisms on risk of radiographic hip and knee osteoarthritis and severity of knee osteoarthritis. - Kerkhof, H; Doherty, M; Arden, N; Abramson, S; Attur, M; Bos, S; Cooper, C; Dennison, E; Doherty, SA; Evangelou, E; Hart, D; Hofman, A; et al. (2011)
To clarify the role of common genetic variation in the Interleukin-1β (IL1B) and Interleukin-1R antagonist (IL1RN) genes on risk of knee and hip osteoarthritis (OA) and severity of knee OA by means of large-scale meta-analyses.